EARLY ANALYSIS OF AUGMENTED REALITY MEDIA ON THE CONCEPT OF OPTICAL SYSTEMS - Widiasih Widiasih; Zakirman Zakirman; Ratna Ekawati; Heni Safitri; Ichwan Ichwan (JURNAL PENDIDIKAN GLASSER, 2023)
The optic system of the eye consists abstract concept. To deepen students' understanding of eye optic systems, appropriate learning media are needed. AR technology provides opportunities to be able to optimize learning and create learning effectiveness. The aim of this research is to produce a valid, practical and effective augmented reality (AR) medium to enhance students' understanding of the concept of eye optic systems. Research method used the ADDIE model, where the following research steps: (1) Analyze (Needsanalysis), (2) Design (Product design),(3) Develop (Product development),(4) Implementation (Implementation and product trials),(5) Evaluation (Product evaluation). From the entire stage of research carried out, obtained viable AR media (valid, practical and effective) to be used in improving students' understanding of the concept of the system optical eye. The external targets that will result from the first year's proposed activities are AR media products on the topic of eye optic systems and are listed in Intellectual Property Rights (IPR). In the second year, the external target of research is to obtain AR media products on the topic of valid optical eye systems based on expert assessments as well as research results that have been published in international conference. The thirdyear, the targeted external is to produce a valid, practical and effective virtual reality media prortype to enhance students' understanding of the concept of optical systems. through implementation and evaluation activities